465 Radiotherapy and CTLA-4 blockade expand anti-tumor T cells differentiation states and cooperate with CD40 agonist to induce tumor rejection. (9th November 2020) - Rudqvist, Nils; Lhuillier, Claire; Charpentier, Maud; Wennerberg, Erik; Spada, Sheila; Sheridan, Caroline; Zhou, Xi Kathy; Zhang, Tuo; Sims, Jennifer; Alonso, Alicia; Demaria, Sandra
Abstract : Background: Radiotherapy (RT) in combination with CTLA-4 inhibition (CTLA4i) can expand and activate T-cells to reject tumors in both mice and some patients with tumors unresponsive to CTLA4i alone. 1 2 However, only a subset of patients achieves long-term control of metastatic disease. Similar responses to RT+CTLA4i are seen in the 4T1 mouse model of triple negative breast cancer (TNBC), making it an ideal model to interrogate the interaction between RT and CTLA4i, and identify barriers to its effectiveness. Methods: Mice were inoculated in one or both flanks with 4T1 cells. In some experiments one tumor was removed for analysis before start of treatment with RT (3 × 8 Gy) and/or anti-CTLA-4 antibody (9H10, 3 × 200 ?g i.p.). The intratumoral T cell response was assessed using bulk and single cell RNA/TCR sequencing. The METABRIC dataset 3 was used to associate gene expression signatures with patient survival. In some experiments, RT+CTLA4i was combined with PD-1, LAG-3, or CD40 Abs. Results: RT, alone and with CTLA4i, increased the TCR repertoire clonality and activated T cells density in the tumors (figure 1A-G). In untreated tumors, Gzmb+Prf1+Lag3+Pd1+Cd8+ T cells (cluster 0) were most common. CTLA4i 'unlocked' Ifng+Cd40lg+ Cd4+ T cells (cluster 2) while RT favored expansion/persistence of Cd8+ T cell clusters. In tumors of mice treated with RT+CTLA4i activated Treg cells (cluster 1) were decreased and Ifng+Cd40lg+Cd4+ T cells (cluster 2) increased. Relatively among CD8+ T cells, Ifng+Tnf+Cd8+ (cluster 4) was expanded at the expense of cluster 0 (figure 2A-F). Gene signatures defining clusters 0, 2, and 4 were associated with improved survival in the METABRIC TNBC patient cohort using a multivariate model (figure 2G-H). In mice, AH1-tumor antigen-specific CD8+ T cells occupied different transcriptional states, with a shift to cluster 4 in mice treated with RT+CTLA4i (figure 2I), suggesting that multiple functional T cell states are required for tumor rejection. Based on the T cell phenotypes expanded by RT+CTLA4i, antibodies to PD-1, LAG-3, and CD40 were tested for the ability to enhance RT+CTLA4i therapy. Only CD40-agonist improved significantly tumor control (figure 3A-B). Conclusions: Altogether, these results revealed that RT and CTLA4i have complementary effects and besides driving T cells into tumors shape CD4 and CD8 T cell functional differentiation towards subsets that are associated with improved survival in patients. Unexpectedly, inhibition of checkpoint receptors expressed by a large CD8 T cells cluster did not further improve responses to RT+CTLA4i, whereas agonistic CD40 therapy did, suggesting new therapeutic strategies. Acknowledgements: Grant support: R01CA198533 References: K, Ferrari de Andrade L, Wucherpfennig KW, Heguy A, Imai N, Gnjatic S, Emerson RO, Zhou XK, Zhang T, Chachoua A, Demaria S. Radiotherapy induces responses of lung cancer to CTLA-4 blockade. Nat Med 2018;24(12):1845–51. Rudqvist NP, Pilones KA, Lhuillier C, Wennerberg E, Sidhom JW, Emerson RO, Robins HS, Schneck J, Formenti SC, Demaria S. Radiotherapy and CTLA-4 Blockade Shape the TCR Repertoire of Tumor-Infiltrating T Cells. Cancer Immunol Res 2018;6(2):139–50. Curtis C, Shah SP, Chin SF, Turashvili G, Rueda OM, Dunning MJ, Speed D, Lynch AG, Samarajiwa S, Yuan Y, Graf S, Ha G, Haffari G, Bashashati A, Russell R, McKinney S, Group M, Langerod A, Green A, Provenzano E, Wishart G, Pinder S, Watson P, Markowetz F, Murphy L, Ellis I, Purushotham A, Borresen-Dale AL, Brenton JD, Tavare S, Caldas C, Aparicio S. The genomic and transcriptomic architecture of 2, 000 breast tumours reveals novel subgroups. Nature 2012;486(7403):346–52.